2010
DOI: 10.5202/rei.v1i1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Financing of Innovative Firms

Abstract: Abstract:To what extent are new and/or innovative firms fundamentally different from established firms, and therefore require a different form of financing? The theoretical background for this proposition is presented, and the empirical evidence on its importance is reviewed. Owing to the intangible nature of their investment, asymmetricinformation and moral-hazard, these firms are more likely to be financed by equity than debt and behave in some cases as though they are cash-constrained, especially if they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(157 citation statements)
references
References 77 publications
6
130
2
7
Order By: Relevance
“…Empirical studies found that factors such as firm size, firm age, ownership structure, profitability, asset structure and industry are important determinants of the demand for and availability of financing instruments (Chittenden and Hutchinson 1996;Frank and Goyal 2007;Howorth 2001;López-Gracia and Sogorb-Mira 2008;Michaelas et al 1999;Romano et al 2001). In addition, a number of studies focused on the financing determinants of specific types of firms like innovative and high-growth companies (Freel 2006;Hall 2010;Mazzucato 2013;Mina et al 2013;Vanacker and Manigart 2010). The results of the cluster analysis contribute to this literature by disclosing that SME financing types are characterised by specific combinations of firm-, product-and industry-specific factors.…”
Section: Theoretical Contributionsmentioning
confidence: 89%
See 3 more Smart Citations
“…Empirical studies found that factors such as firm size, firm age, ownership structure, profitability, asset structure and industry are important determinants of the demand for and availability of financing instruments (Chittenden and Hutchinson 1996;Frank and Goyal 2007;Howorth 2001;López-Gracia and Sogorb-Mira 2008;Michaelas et al 1999;Romano et al 2001). In addition, a number of studies focused on the financing determinants of specific types of firms like innovative and high-growth companies (Freel 2006;Hall 2010;Mazzucato 2013;Mina et al 2013;Vanacker and Manigart 2010). The results of the cluster analysis contribute to this literature by disclosing that SME financing types are characterised by specific combinations of firm-, product-and industry-specific factors.…”
Section: Theoretical Contributionsmentioning
confidence: 89%
“…High-risk projects increase the probability of bankruptcy of the firm, whereas the higher risks are not offset by potentially higher returns for debt providers (Brown and Degryse 2012;Magri 2009). Equity investors, however, participate in the success of the firm and can compensate the higher risks with a potential higher return in the case of success (Carpenter and Petersen 2002a;Hall 2010). Furthermore, VC investors have been found to be better equipped to deal with the higher risks due to their comprehensive due diligence procedures, personal contacts with the entrepreneurs and direct involvement in the firm (Block and Sandner 2009;Carpenter and Petersen 2002a;Cosh et al 2009;Hall 2010;van Osnabrugge 2000).…”
Section: Product-specific Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Data used in this paper and described afterwards, indicate that trade credit accounts on average for 24.9% of firms' total liabilities. Finally, Venture Capital (VC) and, in general, private equity have been extensively studied in recent years since they should provide external finance to firms which are normally excluded from credit market (Hall, 2010). Economic theory highlights the role played by venture capitalists in reducing asymmetric information by intensively screening firms before providing capital and monitoring them afterwards.…”
Section: Introductionmentioning
confidence: 99%